1994
DOI: 10.3109/00016349409023451
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐controlled trial of active immunization with third party leukocytes in recurrent miscarriage

Abstract: Active immunization did not provide any benefit in the overall group of women with recurrent miscarriages. However, among women with primary recurrent miscarriages it may improve outcome with respect to the number of livebirths and birthweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Five hundred and ninety‐two studies were initially screened. Eighteen randomized trials published in thirteen English literatures and five Chinese literatures were used for analysis . For the primary outcome measure, live births, we calculated an odds ratio and its 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Five hundred and ninety‐two studies were initially screened. Eighteen randomized trials published in thirteen English literatures and five Chinese literatures were used for analysis . For the primary outcome measure, live births, we calculated an odds ratio and its 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Carp et al reported that the rate of anomalies in infants was not significantly different between immunized and non-immunized patients [34]. Christiansen et al [35] and Cavalcante et al [36] indicated that the condition of infants born to mothers who had undergone the immunotherapy was not disturbed. We further found that the immunologic parameters were within the normal range in infants born to patients with URA who had undergone the immunotherapy in our serial follow-up study for the infants [37], and Malinowski et al also reported no significant deterioration in the immunologic parameters of infants from patients with URA who had undergone immunization with paternal lymphocytes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of this modality has been controversial, an analysis of controlled clinical trials revealed the efficacy for patients with Unexplained Recurrent Abortion (URA) [7,14,19,26,27], especially for those who were negative for blocking antibodies evaluated by a mixed lymphocyte culture reaction between spouses (MLR-BAbs) [19,22,[28][29][30][31][32][33]. The outcome of pregnancies, especially the condition of infants (such as the body weight of infants or the number of gestational weeks at which the infants were born) of patients after this immunotherapy, has not been fully elucidated, although some articles suggested absence of harmfulness of this immunotherapy for the infants born to immunized patients [34][35][36][37][38][39]. On the other hand, there is possibility that the above-mentioned MLR-BAbs, which are considered to be directed against paternal or fetal antigens, might adversely affect fetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports by other investigators have disputed the efficiency of alloimmunization [20][21][22][23][24][25]. Scott et al, recently reviewed most of controlled trials and concluded that immunotherapies to prevent recurrent miscarriages were not effective [26].…”
Section: To Reject or Not Reject: Alloimmuniza-tion Is The Answermentioning
confidence: 94%